Dependence of microstructural evolution on the geometric structure for serviced DZ125 turbine blades - Xie, Yadan; Zhao, Jianjiang; Fu, Haoran; Wei, Hua (Frontiers in Materials, 2023)
The turbine blades were directionally solidified by a high-rate solidification process by the Bridgman technique using directional solidified Ni-based master superalloy DZ125 and operated on the engine bench with a high-temperature gas environment of more than 1500 °C from combustor and high-speed rotation of more than 13500 rpm for 400 h. A service-environment-based model was put forward to simulate the distribution of temperature and stress on the DZ125 blade in service. It was found that the distribution of temperature and stress on the serviced DZ125 blade was closely related to its geometric structure. The microstructural evolution of the serviced DZ125 blade was analyzed and the variations of microstructures with temperature and stress were investigated by using a scanning electron microscope. The results revealed that the evolution process of microstructures on the serviced DZ125 blade was different from that of the standard sample tested at constant temperature and uniaxial tensile stress. The reason for this discrepancy was explored using a combination of finite-element calculation and diffusion coefficient calculation.